Improvement of Low-Temperature zT in a Mg3 Sb2 -Mg3 Bi2 Solid Solution via Mg-Vapor Annealing - Wood, Maxwell (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.